Automation risks of vocational training programs and early careers in the Netherlands - Alexander Dicks; Annemarie Künn-Nelen; Mark Levels; Raymond Montizaan (Acta Sociologica, 2024)
In this article, we study the role of automation risks in the school-to-work transition (STWT) of secondary vocational education (VET) graduates in the Netherlands. We use a combination of administrative and survey data, enriched with estimates of automation risks. Using sequence analysis, we find four ideal-type school-to-work trajectories representing the first 10 years in the labor market: employment, further education, further VET, and NEET. Multinomial regressions show that automation risk is not consistently associated with the type of school-to-work trajectory. We also investigate the relation between automation risk and starting wages and wage growth. We find that automation risk is negatively associated with starting wages, but not with wage growth.
Keywords: 300; Automation; school-to-work transition; wage growth; vocational education and training; sequence analysis